2002
DOI: 10.1046/j.1356-9597.2001.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperploidy induced by drugs that inhibit formation of microtubule promotes chromosome instability

Abstract: Background : Antimicrotubule drugs (AMDs), such as taxol and vincristine, are the most important addition to the chemotherapeutic armamentarium against human cancers. It has been shown that prolonged AMD treatment induces hyperploidy in G1-checkpoint-defective cancer cells and that these hyperploid cells subsequently undergo apoptosis. However, a fraction of these hyperploid cells are able to survive the prolonged mitotic stress and resume cell-cycle progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
0
17
0
2
Order By: Relevance
“…SIRT2 prevents microtubule poison-induced hyperploid cell formation via a block of entry to chromosome condensation After the prolonged exposure to nocodazole, U251MG cells, which carry a p53 mutation (Alonso et al, 2003), undergo a transient arrest at mitosis and subsequently escape from mitotic arrest and then undergo DNA replication, but they do not complete chromosome segregation and cell division. This phenomenon is termed 'mitotic slippage' and represents a failure to maintain a mitotic arrested state (Di Leonardo et al, 1997;Nitta et al, 2002). As a result of mitotic slippage, U251MG cells undergo DNA re-replication and form hyperploid cells, which are considered to be a frequent precursor of aneuploidy during tumorigenesis (Shackney et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT2 prevents microtubule poison-induced hyperploid cell formation via a block of entry to chromosome condensation After the prolonged exposure to nocodazole, U251MG cells, which carry a p53 mutation (Alonso et al, 2003), undergo a transient arrest at mitosis and subsequently escape from mitotic arrest and then undergo DNA replication, but they do not complete chromosome segregation and cell division. This phenomenon is termed 'mitotic slippage' and represents a failure to maintain a mitotic arrested state (Di Leonardo et al, 1997;Nitta et al, 2002). As a result of mitotic slippage, U251MG cells undergo DNA re-replication and form hyperploid cells, which are considered to be a frequent precursor of aneuploidy during tumorigenesis (Shackney et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…When considering the therapeutic context, it should be noted that in the U251MG cells, SIRT2 blocks entry to chromosome condensation and subsequent mitotic slippage, and in turn, the DNA re-replication that promotes CIN, including both numerical and structural chromosomal changes (Nitta et al, 2002). Particularly, the formation of hyperploid cells was at least partially prevented by exogenous expression of SIRT2 in U251MG cells, which harbor a p53 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…As a working hypothesis, it is tempting to assume that one of the mechanisms that contribute to oncogenesis may be what we might call a 'cytogenetic catastrophe'. Aneuploidization could result from the asymmetric division of polyploid cells, generated from an illicit cell fusion, as it may occur in vivo (DeWitt and Knight, 2002;Terada et al, 2002;Wurmser and Gage, 2002;Vassilopoulos et al, 2003) or from endoreplication/endomitosis (Nitta et al, 2003). Indeed, polyploidy is frequently observed in neoplasia and constitutes a negative prognostic factor, while aneuploidy is a near-to-general characteristic of cancer (Slovak et al, 2000;Choma et al, 2001;Jallepalli and Lengaue, 2001;Shih et al, 2001;Lingle et al, 2002;Masuda and Takahashi, 2002a, b;Sen et al, 2002;Tort et al, 2003).…”
Section: Mitotic Catastrophe and The Apoptotic Machinerymentioning
confidence: 99%
“…A number of studies have demonstrated that the suppression of survivin results in cells with multipolar mitotic spindles that are either multinucleated or aneuploid (Li et al, 1999;Beltrami et al, 2004;Kappler et al, 2004). Some studies have also indicated that aneuploidy promotes chromosome instability (CIN) in glioma and cervical carcinoma cells (Nitta et al, 2002;Olaharski et al, 2006).…”
mentioning
confidence: 99%